2015
DOI: 10.4028/www.scientific.net/amm.713-715.2556
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Engineering and 3D Printing Technology's Application in Sculpture and the Restoration

Abstract: To elucidate the mechanism that the software Gemagic Studio and 3D printer have an important role in repairing and copying the ancient cultural relics and the damaged sculpture, we take the damaged sculpture, Sissi, as the example, repaired it based on reverse engineering, 3D scanning technology and modern 3D printing technology. In the process of research, we obtain the point data of it, using reverse engineering software Gemagic Studio for the noise removing, compaction, hole filling, surface repair, error r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Potters exude free spirit and artistic attainments to further explore the qualities of ceramics, and establish an art form that conforms to modern aesthetic requirements and trends [6][7][8]. Modern ceramic artists have given contemporary ceramics an unprecedented meaning to re-conceptualize and rediscover the value of ceramics [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Potters exude free spirit and artistic attainments to further explore the qualities of ceramics, and establish an art form that conforms to modern aesthetic requirements and trends [6][7][8]. Modern ceramic artists have given contemporary ceramics an unprecedented meaning to re-conceptualize and rediscover the value of ceramics [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Employing both 3D printing and photogrammetry, Swearingen et al helped to maximize the value that both designers and artists can add [116]. Using 3D scanning/printing technology to repair a damaged sculpture, Wang et al used reverse engineering software with wonderful results [117]. Through a dialectical analysis of technology and art in sculpture creation, Du [118] concluded that the art of sculpture should fully integrate, accept and utilize three-dimensional digital modeling technology, instead of treating it with an opposing attitude.…”
mentioning
confidence: 99%